Composite adhesive and masking forming method
By using composite glue, including pyrolytic glue and protective glue, combined with thermal expansion microbubble technology, the problem that the existing shielding film cannot fully cover the complex structural surface and the difficulty of automated tearing film is solved, and the complete coverage and automatic glue removal of complex structural surfaces are achieved.
Patent Information
- Application Number
- CN202411774601.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-04
- Publication Date
- 2025-04-01
AI Technical Summary
The existing shielding film cannot be fully covered on complex structural surfaces, and it is difficult to automatically tear the film.
Compound glue, including pyrolytic glue and protective glue, is used to form a pyrolytic glue layer and protective glue layer through photocuring, and use thermally expanded microbubbles to achieve automatic glue removal. The composition of the pyrolytic glue layer includes isoborna acrylate monomer, prepolymer, initiator, oxygen barrier, crosslinking agent and thermally expanded microbubbles, and the composition of the protective glue layer includes isoborna acrylate monomer, prepolymer, initiator, oxygen barrier, crosslinking agent and other additives.
Complete coverage and automatic glue removal of complex structural surfaces are achieved, the coverage and versatility of masking glue are improved, and problems such as bubbles and wrinkles are avoided.
Smart Images

Figure CN119736022A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of adhesives, and in particular to a method for forming a composite adhesive and a mask. Background Art
[0002] In the prior art, shielding films are often used to shield the parts of the components that need to be protected, so as to avoid the parts that need to be protected from being exposed and affecting their appearance and performance. In particular, for battery trays, it is more necessary to use a film shielding process to avoid oxidation and corrosion of the battery tray during processes such as anodizing.
[0003] However, existing masking films have the following problems: for complex structures, such as but not limited to uneven structural surfaces, the film cannot cover all the surfaces that need to be covered when applied. In addition, it is difficult to achieve automatic film removal without damaging or scratching the product structure. Summary of the invention
[0004] In view of this, the present application provides a method for forming a composite adhesive and a mask that can solve the above-mentioned technical problems.
[0005] The first aspect of the present application provides a composite adhesive, wherein the composite adhesive comprises a pyrolytic adhesive and a protective adhesive. The composition of the pyrolytic adhesive includes: 60 wt% to 80 wt% of isobornyl acrylate monomer, 5 wt% to 15 wt% of prepolymer, 0.1 wt% to 1.5 wt% of initiator, 1 wt% to 3 wt% of oxygen barrier, 1 wt% to 8 wt% of crosslinking agent, 10 wt% to 20 wt% of thermal expansion microbubbles, and 0 wt% to 2 wt% of other auxiliary agents; The thermal expansion microbubble comprises an outer shell and a hydrocarbon gas enclosed within the outer shell; The protective glue comprises: 65 wt% to 85 wt% of isobornyl acrylate monomer, 5 wt% to 15 wt% of prepolymer, 0.1 wt% to 1.5 wt% of initiator, 1 wt% to 5 wt% of antioxidant, 1 wt% to 10 wt% of crosslinking agent, and 0 wt% to 5 wt% of other auxiliary agents.
[0006] Further, the shell of the heat-expandable microbubble comprises a thermoplastic material, and the hydrocarbon gas comprises at least one of alkanes, olefins, alkynes or cyclic hydrocarbons.
[0007] Furthermore, the average diameter of the thermally expandable microbubbles is 10 μm to 45 μm.
[0008] Furthermore, the thickness of the pyrolytic adhesive layer is A, and the thickness of the protective adhesive layer is B, wherein A and B satisfy the relationship: 1.1≤A / B≤1.6.
[0009] Furthermore, the pyrolytic adhesive layer includes a first surface and a second surface relative to each other, and a first side surface and a second side surface connecting the first surface and the second surface, the first side surface and the second side surface are arranged opposite to each other, and the protective adhesive layer covers the first surface, the first side surface and the second side surface.
[0010] Further, the protective adhesive layer includes a third side and a fourth side relative to each other, the third side and the first side are located on the same side of the composite adhesive, the fourth side and the second side are located on the same side of the composite adhesive, the distance between the first side and the second side is W1, and the distance between the third side and the fourth side is W2, wherein W1 and W2 satisfy the relationship: 0.81≤W1 / W2≤0.91.
[0011] Furthermore, the composite adhesive satisfies at least one of the following conditions: (1) The prepolymer comprises an acrylic acid prepolymer; (2) The initiator includes at least one azo initiator; (3) The oxygen inhibitor includes at least one of the phosphite-based oxygen inhibitors; (4) The cross-linking agent includes at least one of polyisocyanate and its derivatives; (5) The other auxiliary agents include at least one of a surfactant or a thickener.
[0012] A second aspect of the present application provides a method for forming a shield, comprising the following steps: A pyrolytic adhesive is applied on the surface of the area to be shielded, and the pyrolytic adhesive is photocured to form a pyrolytic adhesive layer, wherein the composition of the pyrolytic adhesive includes: 60wt%~80wt% of isobornyl acrylate monomer, 5wt%~15wt% of prepolymer, 0.1wt%~1.5wt% of initiator, 1wt%~3wt% of oxygen barrier, 1wt%~8wt% of crosslinking agent, 10wt%~20wt% of thermal expansion microbubbles, and 0wt%~2wt% of other additives; the thermal expansion microbubbles include an outer shell and a hydrocarbon gas encapsulated inside the outer shell; A protective adhesive is applied on the surface of the pyrolytic adhesive layer, and the protective adhesive is photocured to form a protective adhesive layer, and the protective adhesive layer wraps the pyrolytic adhesive layer to form a composite adhesive to cover the area to be shielded, and the protective adhesive comprises: 65wt%~85wt% of isobornyl acrylate monomer, 5wt%~15wt% of prepolymer, 0.1wt%~1.5wt% of initiator, 1wt%~5wt% of antioxidant, 1wt%~10wt% of cross-linking agent, and 0wt%~5wt% of other additives.
[0013] Further, a dispensing process is used to apply a pyrolytic adhesive on the surface of the area to be shielded, and the temperature of the dispensing process is 38° C. to 60° C.; and / or, The mask forming method further includes heating the composite adhesive to remove the composite adhesive.
[0014] Furthermore, the temperature for heating the composite adhesive is 100°C to 140°C.
[0015] The composite adhesive provided in the present application includes a pyrolytic adhesive and a protective adhesive. The composition of the pyrolytic adhesive includes 60wt%~80wt% of isobornyl acrylate monomer, 5wt%~15wt% of prepolymer, 0.1wt%~1.5wt% of initiator, 1wt%~3wt% of antioxidant, 1wt%~8wt% of cross-linking agent, 10wt%~20wt% of thermal expansion microbubbles, and 0wt%~2wt% of other additives. The composition of the protective adhesive includes 65wt%~85wt% of isobornyl acrylate monomer, 5wt%~15wt% of prepolymer, 0.1wt%~1.5wt% of initiator, 1wt%~5wt% of antioxidant, 1wt%~10wt% of cross-linking agent, and 0wt%~5wt% of other additives. The formula makes the pyrolytic adhesive and the protective adhesive fluid. Therefore, the pyrolytic adhesive layer and the protective adhesive layer obtained after the pyrolytic adhesive and the protective adhesive are cured can cover the surface of the structure to be shielded through a dispensing process, and the pyrolytic adhesive or the protective adhesive can fully cover the surface of the complex structure. When the adhesive layer needs to be removed, the composite adhesive is heated, and the hydrocarbon gas in the heat-expandable microbubbles expands due to the heat, so that the pyrolytic adhesive layer can be separated from the surface of the object to be masked, thereby realizing automatic debonding. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 An exploded view of the composite adhesive and substrate provided in one embodiment of the present application.
[0017] Figure 2 A schematic cross-sectional view of a composite adhesive and a substrate provided in one embodiment of the present application.
[0018] Figure 3 This is a physical picture of covering the workpiece to be masked with composite adhesive in one embodiment of the present application.
[0019] Figure 4 This is a physical picture of the composite adhesive being ready to be separated from the surface of the area to be shielded when the composite adhesive is heated according to one embodiment of the present application.
[0020] Figure 5 This is a physical picture of the composite adhesive after automatic debonding according to one embodiment of the present application.
[0021] Main component symbols The following specific implementation manner will further illustrate the present invention in conjunction with the above-mentioned drawings. DETAILED DESCRIPTION
[0022] The embodiments of the present application are described in detail below. The embodiments described below with reference to the accompanying drawings are exemplary and are only used to explain the present application, and cannot be understood as limiting the present application. The reagents and materials described in the following embodiments can all be obtained from commercial sources.
[0023] See also Figure 1 The present application provides a composite adhesive 10, which includes a pyrolytic adhesive and a protective adhesive.
[0024] The composition of the pyrolytic adhesive includes: 60 wt%~80wt% of isobornyl acrylate monomer, 5 wt%~15wt% of prepolymer, 0.1 wt%~1.5wt% of initiator, 1 wt%~3wt% of antioxidant, 1 wt%~8wt% of cross-linking agent, 10 wt%~20wt% of thermal expansion microbubbles, and 0 wt%~2wt% of other additives.
[0025] The isobornyl acrylate monomer, prepolymer, initiator, oxygen barrier, crosslinking agent, thermal expansion microbubble and other components can be mixed in the above ratio to obtain a pyrolytic adhesive with fluidity, and the fluidity can be better under conditions of heating, pressurization, etc. Compared with the traditional tape, the use of fluid to mask the structure of the substrate 40 can completely overcome the limitation of the shape of the structure surface to be masked, and can achieve complete coverage for the uneven structure surface, thereby improving the coverage rate and versatility of the masking adhesive, and it is not easy to produce bubbles and wrinkles.
[0026] In some embodiments, the content of isobornyl acrylate monomer can be 60wt%, 65wt%, 70wt%, 75wt%, 80wt% or any value within the range formed by any two of the above values. The content of prepolymer can be 5wt%, 8wt%, 10wt%, 13wt%, 15wt% or any value within the range formed by any two of the above values. The content of initiator can be 0.1wt%, 0.5wt%, 1.0wt%, 1.5wt% or any value within the range formed by any two of the above values. The content of oxidation inhibitor can be 1wt%, 1.5wt%, 2wt%, 2.5wt%, 3wt% or any value within the range formed by any two of the above values. The content of crosslinking agent can be 1wt%, 2wt%, 3wt%, 4wt%, 5wt%, 6wt%, 7wt%, 8wt% or any value within the range formed by any two of the above values. The content of thermal expansion microbubbles can be 10wt%, 12wt%, 14wt%, 16wt%, 18wt%, 20wt% or any value within the range formed by any two of the above values.
[0027] In some embodiments, the composition of the pyrolytic adhesive may further include other additives, such as surfactants or thickeners, etc. The mass percentage of other additives to the pyrolytic adhesive may be 0.1wt%, 0.5wt%, 1wt%, 1.5wt%, 2wt% or any value within the range formed by any two of the above values.
[0028] The protective glue comprises: 65 wt%~85wt% of isobornyl acrylate monomer, 5 wt%~15wt% of prepolymer, 0.1 wt%~1.5wt% of initiator, 1 wt%~5wt% of antioxidant, 1 wt%~10wt% of crosslinking agent, and 0 wt%~5wt% of other additives.
[0029] The components such as acrylic acid isobornyl ester monomer, prepolymer, initiator, oxygen inhibitor, cross-linking agent can be mixed in the above ratio to obtain a protective adhesive with fluidity, so the protective adhesive can also achieve complete shielding of different structures of different substrates 40, and the shielding coverage and versatility are improved, and it is not easy to produce bubbles and wrinkles. In addition, the protective adhesive also contains acrylic acid isobornyl ester monomer. The carbon-carbon double bond on the acrylic acid isobornyl ester monomer can copolymerize with many unsaturated monomers through free radical polymerization. The acrylic acid isobornyl ester monomer has an ester group and a non-polar cycloalkyl group. The ester group and the non-polar cycloalkyl group provide strong steric hindrance protection to the polymer chain, so that the protective adhesive has excellent water resistance, toughness, acid and alkali resistance, and adhesion. Therefore, the protective adhesive can well cover and protect the pyrolytic adhesive and the area to be shielded on the substrate 40.
[0030] In some embodiments, the content of isobornyl acrylate monomer can be 65wt%, 70wt%, 75wt%, 80wt%, 85wt% or any value within the range formed by any two of the above values. The content of prepolymer can be 5wt%, 8wt%, 10wt%, 13wt%, 15wt% or any value within the range formed by any two of the above values. The content of initiator can be 0.1wt%, 0.5wt%, 1.0wt%, 1.5wt% or any value within the range formed by any two of the above values. The content of oxidation inhibitor can be 1wt%, 2wt%, 3wt%, 4wt%, 5wt% or any value within the range formed by any two of the above values. The content of crosslinking agent can be 1wt%, 2wt%, 4wt%, 6wt%, 8wt%, 10wt% or any value within the range formed by any two of the above values.
[0031] In some embodiments, the protective colloid may further include other additives, such as surfactants or thickeners, etc. The mass percentage of other additives in the protective colloid may be 0.1 wt%, 1 wt%, 2 wt%, 3 wt%, 4 wt%, 5 wt%, or any value within the range formed by any two of the above values.
[0032] The composition ratio of the pyrolytic adhesive and the protective adhesive is within the above range, so that the protective adhesive layer 30 formed by the curing of the protective adhesive has good water resistance, toughness, acid and alkali resistance, adhesion and other properties, and can also ensure that the pyrolytic adhesive layer 20 formed by the curing of the pyrolytic adhesive can generate sufficient expansion force when heated to support the protective adhesive layer 30, thereby achieving the effect of automatic debonding.
[0033] In some embodiments, in the composition of the pyrolytic adhesive or protective adhesive, the prepolymer includes an acrylic prepolymer. In some embodiments, the initiator includes one or more of azo initiators. In some embodiments, the oxidation inhibitor includes one or more of phosphite oxidation inhibitors. In some embodiments, the crosslinking agent includes one or more of polyisocyanates and their derivatives.
[0034] In the composition of the pyrolysis glue, the heat-expanding microbubbles help the pyrolysis glue layer 20 to quickly support the protective glue layer 30 under low-temperature heating conditions, so that the two can be completely separated from the surface of the substrate 40. There are huge non-polar side groups on the polymer chain obtained after the polymerization of the acrylic acid isobornyl ester monomer in the pyrolysis glue, which weakens the interaction between the molecular chains, reduces the viscosity of the polymer, improves the compatibility of the polymer colloid with the heat-expanding microbubbles, and enables the heat-expanding microbubbles to be evenly dispersed in the polymer colloid. By compounding the protective glue layer 30 and the pyrolysis glue layer 20, the best shielding effect and the effect of automatic debonding can be obtained.
[0035] The heat-expandable microbubble comprises a shell and a hydrocarbon gas enclosed in the shell.
[0036] In some embodiments, the shell of the heat-expandable microbubble comprises a thermoplastic material, and the hydrocarbon gas comprises at least one of alkanes, alkenes, alkynes, or cyclohydrocarbons, such as methane, ethane, propane, butane, ethylene, propylene, butene, acetylene, cyclopropane, or cyclobutane.
[0037] In some embodiments, for thermoplastic materials, hydrophilic functional groups, including but not limited to -OH, -COOH, -NH2, -CHO, etc., can be added to their chain segments by suspension polymerization to increase the compatibility of the heat-expandable microbubbles with the colloid, so that the heat-expandable microspheres are more evenly dispersed in the colloid.
[0038] In some embodiments, the average diameter of the heat-expandable microbubbles is 10 μm to 45 μm. For example, the average diameter of the heat-expandable microbubbles can be 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, 45 μm, or any value within the range formed by any two of the above values. The average diameter of the heat-expandable microbubbles is within the above range, so that the heat-expandable microbubbles are more evenly dispersed in the pyrolysis glue, and the heat-expandable microbubbles are more likely to support the protective glue layer 30 after expansion.
[0039] In some embodiments, the pyrolytic adhesive is cured to form a pyrolytic adhesive layer 20, and the protective adhesive is cured to form a protective adhesive layer 30. The thickness of the pyrolytic adhesive layer 20 is A, and the thickness of the protective adhesive layer 30 is B, and 1.1≤A / B≤1.6. For example, A / B can be 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, or any value within the range formed by any two of the above values. The thickness ratio of the pyrolytic adhesive layer 20 to the protective adhesive layer 30 is within the above range, which helps to further ensure that the expansion force of the pyrolytic adhesive layer 20 can successfully support the protective adhesive layer 30, thereby achieving the effect of automatic debonding.
[0040] In some embodiments, see Figure 2 The pyrolytic adhesive layer 20 includes a first surface 21 and a second surface 22 opposite to each other, and a first side surface 23 and a second side surface 24 connecting the first surface 21 and the second surface 22. The first side surface 23 and the second side surface 24 are arranged opposite to each other, and the protective adhesive layer 30 covers the first surface 21, the first side surface 23 and the second side surface 24. In this way, the protective adhesive layer 30 can completely cover the pyrolytic adhesive layer 20, thereby enhancing the shielding effect of the composite adhesive 10.
[0041] In some embodiments, see Figure 2 The protective adhesive layer 30 includes a third side surface 31 and a fourth side surface 32 opposite to each other. The third side surface 31 and the first side surface 23 are located on the same side of the composite adhesive 10. The fourth side surface 32 and the second side surface 24 are located on the same side of the composite adhesive 10. The distance between the first side surface 23 and the second side surface 24 is W1, and the distance between the third side surface 31 and the fourth side surface 32 is W2. 0.81≤W1 / W2≤0.91. For example, W1 / W2 can be 0.81, 0.84, 0.88, 0.91 or any value within the range formed by any two of the above values. When the value of W1 / W2 is within the above range, it can be ensured that the protective adhesive layer 30 can completely cover the pyrolytic adhesive layer 20, and at the same time, it can also ensure that the composite adhesive 10 can be automatically peeled off after being heated.
[0042] In the present application, the “thickness of the pyrolytic adhesive layer 20 ” refers to the average vertical distance between the first surface 21 and the second surface 22 along the thickness direction, and the “thickness of the protective adhesive layer 30 ” refers to the average vertical distance between the surface of the protective adhesive layer 30 facing away from the first surface 21 and the first surface 21 along the thickness direction.
[0043] The composite adhesive 10 provided in the present application can be used in processes such as anodizing, sandblasting, physical vapor deposition, electroplating, and dispensing, and can shield the parts of the substrate 40 that need to be protected.
[0044] See also Figure 1 and Figure 2 The present application also provides a method for forming a shield, comprising the following steps: A pyrolytic adhesive is applied to the surface of the area to be shielded of the substrate 40, and the pyrolytic adhesive is photocured to form a pyrolytic adhesive layer 20, wherein the composition of the pyrolytic adhesive includes: 60wt%~80wt% of isobornyl acrylate monomer, 5wt%~15wt% of prepolymer, 0.1wt%~1.5wt% of initiator, 1wt%~3wt% of oxygen barrier, 1wt%~8wt% of crosslinking agent, 10wt%~20wt% of thermal expansion microbubbles, and 0wt%~2wt% of other additives; the thermal expansion microbubbles include an outer shell and a hydrocarbon gas encapsulated in the inner shell; A protective adhesive is applied to the surface of the pyrolytic adhesive layer 20 away from the area to be shielded, and the protective adhesive is photocured to form a protective adhesive layer 30. The protective adhesive layer 30 wraps the pyrolytic adhesive layer 20 to form a composite adhesive 10 to shield the area to be shielded. The composition of the protective adhesive includes: 65wt%~85wt% of isobornyl acrylate monomer, 5wt%~15wt% of prepolymer, 0.1wt%~1.5wt% of initiator, 1wt%~5wt% of antioxidant, 1wt%~10wt% of cross-linking agent, and 0wt%~5wt% of other additives.
[0045] In some embodiments, the surface of the area to be shielded may be a smooth surface, a sandblasted surface, a brushed surface, etc. The composite adhesive 10 provided in the present application may be used for surfaces of any roughness. The surface of the area to be shielded may be a flat surface, a concave-convex surface, a curved surface, etc. The composite adhesive 10 provided in the present application may be applicable to surfaces of various shapes.
[0046] In some embodiments, a dispensing process is used to apply pyrolytic glue on the surface of the area to be masked, and the temperature of the dispensing process is 38°C to 60°C. For example, the temperature of the dispensing process can be 38°C, 40°C, 45°C, 50°C, 55°C, 60°C, or any value within the range formed by any two of the above values. The temperature of the dispensing process is the temperature of the dispensing valve body. Applying temperature during dispensing can make the pyrolytic glue and protective glue have good fluidity, so as to achieve better masking effect on the surface of complex structures. According to the composition ratio of the pyrolytic glue and the protective glue, the temperature of the dispensing process is within the above range, which can make the pyrolytic glue and the protective glue have suitable fluidity.
[0047] In some embodiments, the dispensing process can use a dispensing device containing a precision valve body such as a piezoelectric valve, a spray valve or a pneumatic valve. The use of automated dispensing equipment helps to improve the positioning accuracy of dispensing, avoiding the problems of low film sticking accuracy and poor stability caused by the uneven technical level of skilled workers in the traditional manual film sticking method. In addition, the use of precision valve bodies such as piezoelectric valves, spray valves or pneumatic valves is conducive to accurately controlling the thickness of the glue layer.
[0048] In some embodiments, the viscosity of the pyrolytic adhesive is 1800cps-2200cps, the thixotropic index of the pyrolytic adhesive is 1.1-1.2, and the shrinkage rate of the pyrolytic adhesive is less than 2%. The viscosity and thixotropic index of the pyrolytic adhesive are within the above ranges, so that it can be applied to the dispensing equipment without causing problems such as glue hanging and valve body clogging.
[0049] In some embodiments, the viscosity of the protective glue is 18000cps-24000cps, the thixotropic index of the protective glue is 1.9-2.0, and the shrinkage rate of the protective glue is less than 2%, so that the shear strength of the protective glue is greater than 4.4Mpa, and the elongation at break is in the range of 110%-115%. That is, the protective glue layer 30 has good adhesion and toughness.
[0050] In some embodiments, the method of use further includes heating the composite adhesive 10 to remove the composite adhesive 10 .
[0051] In some embodiments, the temperature at which the composite adhesive 10 is heated is 100°C to 140°C. For example, the temperature at which the composite adhesive 10 is heated can be 100°C, 110°C, 120°C, 130°C, 140°C, or any value within the range formed by any two of the above values. The heating temperature range of the composite adhesive 10 matches the composition ratio of the composite adhesive 10. By heating the composite adhesive 10 locally at 100°C to 140°C, the outer shell of the heat-expandable microbubbles is softened by heat, and the gas inside the heat-expandable microbubbles expands, and the volume of the gas rapidly expands to dozens of times the original volume. The expansion force generated by the gas expansion causes the pyrolytic adhesive layer 20 to support the protective adhesive layer 30. Since the protective adhesive layer 30 covers and bonds the pyrolytic adhesive layer 20, the protective adhesive layer 30 will detach from the surface of the area to be shielded together with the pyrolytic adhesive layer 20, thereby achieving the purpose of automatic debonding, and no residual adhesive will be left on the surface of the area to be shielded.
[0052] The composite adhesive 10 provided in the present application can be used in the fields of bonding, fixing and sealing electronic products, hole shielding, circuit board shielding and process shielding.
[0053] The technical solution of the present application is further explained below in conjunction with specific implementation methods.
[0054] Example 1 S1: A pyrolytic adhesive is prepared according to a ratio of 70wt% isobornyl acrylate monomer, 18wt% heat-expandable microbubbles, 8wt% acrylic prepolymer, 1wt% azo initiator, 1wt% phosphite antioxidant and 2wt% polyisocyanate, wherein the shell material of the heat-expandable microbubbles is thermoplastic resin polymethyl methacrylate, the gas enclosed by the shell is CH4, and the average diameter of the heat-expandable microbubbles is 20μm.
[0055] The protective adhesive is prepared according to the ratio of 80wt% of isobornyl acrylate monomer, 11wt% of acrylic prepolymer, 1wt% of azo initiator, 3wt% of phosphite antioxidant and 5wt% of polyisocyanate.
[0056] S2: Provide a mobile phone middle frame, and use a dispensing device with a piezoelectric valve to apply pyrolytic adhesive to the battery slot area to be protected in the battery slot area of the mobile phone middle frame, control the thickness A of the pyrolytic adhesive to be 0.2 mm, and use ultraviolet light to cure the pyrolytic adhesive to form a pyrolytic adhesive layer 20. The set temperature of the piezoelectric valve is 50° C., and the set air pressure of the piezoelectric valve is 200 kPa.
[0057] S3: Protective glue is applied to the surface of the pyrolytic glue layer 20 away from the battery slot area through a piezoelectric valve, and the thickness B of the protective glue layer 30 is controlled to be 0.15 mm, the distance W1 between the first side 23 and the second side 24 is 39 mm, and the distance W2 between the third side 31 and the fourth side 32 is 43 mm. The protective glue is cured with ultraviolet light again to obtain a protective glue layer 30. The protective glue layer 30 is compounded with the pyrolytic glue layer 20 to form a composite glue 10.
[0058] S4: The composite adhesive 10 is locally heated at a temperature of 110° C. After heating for a period of time, it can be seen that the composite adhesive 10 is automatically peeled off from the battery slot area.
[0059] See also Figure 3~Figure 5 , Figure 3 The actual picture showing the composite adhesive 10 formed in the battery slot area shows that the composite adhesive 10 can completely cover the area to be shielded of the battery slot, and there is no dead corner that cannot be covered. Figure 4 The figure shows that after the composite adhesive 10 is locally heated, the heat-expanding microbubbles in the pyrolytic adhesive layer 20 begin to expand in volume, and the gas expansion causes the composite adhesive 10 to form bubbles on the surface of the battery slot area ( Figure 4 The slightly whiter areas in the middle are bubbles, e.g. Figure 4 ), which is indicated by the oval dotted frame in the figure, indicating that the pyrolytic adhesive layer 20 begins to peel off the protective adhesive layer 30 from the surface of the area to be shielded in the battery slot through the expansion force of the gas expansion. Figure 5What is shown is a real picture after the composite adhesive 10 is completely peeled off from the surface of the area to be shielded in the battery slot. It can be seen that the composite adhesive 10 curls up by itself after automatic peeling and still maintains its complete shape. The pyrolytic adhesive layer 20 and the protective adhesive layer 30 are not damaged, which means that the composite adhesive 10 can be automatically debonded by heat and no residual adhesive is left on the surface of the battery slot.
[0060] <Performance Test> Average edge erosion width (D): After the composite adhesive 10 has been subjected to the sandblasting, anodizing and filling processes, the average erosion width of the edge of the composite adhesive 10 is measured using a Keyence instrument.
[0061] Whether the adhesive can be automatically debonded: After heating the composite adhesive 10 locally at a fixed temperature, observe whether the composite adhesive 10 can be automatically debonded.
[0062] Embodiment 2 to Embodiment 6 The difference from Example 1 is the thickness A of the pyrolytic adhesive layer 20, the thickness B of the protective adhesive layer 30, the ratio A / B, the distance W1 between the first side 23 and the second side 24, the distance W2 between the third side 31 and the fourth side 32, and the ratio W1 / W2. Please refer to Table 1 for details.
[0063] Table 1 It can be seen from Table 1 that by controlling the appropriate ratio of the thickness A of the pyrolytic adhesive layer 20 to the thickness B of the protective adhesive layer 30 and the ratio of the distance W1 between the first side 23 and the second side 24 to the distance W2 between the third side 31 and the fourth side 32, a composite adhesive 10 with good protection and automatic debonding can be obtained, and the average edge erosion width D is less than or equal to 0.42 mm, while the average edge erosion width of the existing masking film is about 1.1 mm. In comparison, it can be seen that the composite adhesive 10 provided in the present application has a better shielding effect.
[0064] Embodiment 7 to Embodiment 9 The difference from Example 1 is that the heating temperature of the composite adhesive 10 is different, see Table 2 for details.
[0065] Table 2 It can be seen from Table 2 that the heating temperature of the composite adhesive 10 is appropriate, which is conducive to the automatic debonding of the composite adhesive 10 and the debonding time is appropriate. If the heating temperature is too low, the time required for automatic debonding will be too long, that is, the debonding speed is slow.
[0066] The above implementation modes are only used to illustrate the technical solutions of the present application and are not intended to limit the present application. Although the present application is described in detail with reference to the above implementation modes, a person skilled in the art should understand that the technical solutions of the present application may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present application.
Claims
1. A composite adhesive, characterized in that: The composite adhesive comprises a pyrolytic adhesive and a protective adhesive. The composition of the pyrolytic adhesive includes: 60wt%~80wt% of isobornyl acrylate monomer, 5wt%~15wt% of prepolymer, 0.1wt%~1.5wt% of initiator, 1wt%~3wt% of antioxidant, 1wt%~8wt% of crosslinking agent, 10wt%~20wt% of thermal expansion microbubbles, and 0wt%~2wt% of other additives; The thermal expansion microbubble comprises a shell and a hydrocarbon gas enclosed within the shell; The protective glue comprises: 65wt%-85wt% of isobornyl acrylate monomer, 5wt%-15wt% of prepolymer, 0.1wt%-1.5wt% of initiator, 1wt%-5wt% of antioxidant, 1wt%-10wt% of crosslinking agent, and 0wt%-5wt% of other auxiliary agents.
2. The composite adhesive according to claim 1, characterized in that: The shell of the heat-expandable microbubble comprises a thermoplastic material, and the hydrocarbon gas comprises at least one of alkanes, olefins, alkynes or cyclic hydrocarbons.
3. The composite adhesive according to claim 1, characterized in that: The average diameter of the thermal expansion microbubbles is 10 μm to 45 μm.
4. The composite adhesive according to claim 1, characterized in that: The pyrolytic adhesive is cured to form a pyrolytic adhesive layer, and the protective adhesive is cured to form a protective adhesive layer. The thickness of the pyrolytic adhesive layer is A, and the thickness of the protective adhesive layer is B, wherein A and B satisfy the relationship: 1.1≤A / B≤1.
6.
5. The composite adhesive according to claim 4, characterized in that: The pyrolytic adhesive layer includes a first surface and a second surface opposite to each other, and a first side surface and a second side surface connecting the first surface and the second surface. The first side surface and the second side surface are arranged opposite to each other, and the protective adhesive layer covers the first surface, the first side surface and the second side surface.
6. The composite adhesive according to claim 5, characterized in that: The protective adhesive layer includes a third side and a fourth side facing each other, the third side and the first side are located on the same side of the composite adhesive, the fourth side and the second side are located on the same side of the composite adhesive, the distance between the first side and the second side is W1, and the distance between the third side and the fourth side is W2, wherein W1 and W2 satisfy the relationship: 0.81≤W1 / W2≤0.
91.
7. The composite adhesive according to claim 1, characterized in that: The composite adhesive at least meets one of the following conditions: (1) The prepolymer comprises an acrylic acid prepolymer; (2) The initiator includes at least one azo initiator; (3) The oxygen inhibitor includes at least one of the phosphite-based oxygen inhibitors; (4) The cross-linking agent includes at least one of polyisocyanate and its derivatives; (5) The other auxiliary agents include at least one of a surfactant or a thickener.
8. A method for forming a shield, characterized in that: The following steps are involved: A pyrolytic adhesive is applied on the surface of the area to be shielded, and the pyrolytic adhesive is photocured to form a pyrolytic adhesive layer, wherein the composition of the pyrolytic adhesive includes: 60wt%~80wt% of isobornyl acrylate monomer, 5wt%~15wt% of prepolymer, 0.1wt%~1.5wt% of initiator, 1wt%~3wt% of oxygen barrier, 1wt%~8wt% of crosslinking agent, 10wt%~20wt% of thermal expansion microbubbles, and 0wt%~2wt% of other additives; the thermal expansion microbubbles include an outer shell and a hydrocarbon gas encapsulated inside the outer shell; A protective adhesive is applied on the surface of the pyrolytic adhesive layer, and the protective adhesive is photocured to form a protective adhesive layer, and the protective adhesive layer wraps the pyrolytic adhesive layer to form a composite adhesive to cover the area to be shielded, and the protective adhesive comprises: 65wt%~85wt% of isobornyl acrylate monomer, 5wt%~15wt% of prepolymer, 0.1wt%~1.5wt% of initiator, 1wt%~5wt% of antioxidant, 1wt%~10wt% of cross-linking agent, and 0wt%~5wt% of other additives.
9. The method for forming a shield according to claim 8, characterized in that: Using a dispensing process to apply pyrolytic glue on the surface of the area to be shielded, the temperature of the dispensing process is 38° C. to 60° C.; and / or, The mask forming method further includes heating the composite adhesive to remove the composite adhesive.
10. The method for forming a shield according to claim 9, characterized in that: The temperature of heating the composite adhesive is 100° C. to 140° C.